PENGARUH PROFITABILITAS, KEPEMILIKAN MANAJERIAL, PERTUMBUHAN PERUSAHAAN, EFEKTIVITAS USAHA, DAN INVESTMENT OPPORTUNITY SET TERHADAP KEBIJAKAN DIVIDEN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia pada Periode 2013-2015) - Aisyah Maulyantini; Novita Indrawati; Pipin Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to determine the effect of profitability, managerial ownership, corporate growth, business effectiveness, and Investment Opportunity Set of Dividend Policy. The population used in this study is a manufacturing company listed on the Indonesia Stock Exchange in 2013, 2014, 2015. Sampling method used is purposive sampling method. Based on the criteria, the sample in this study amounted to 23 companies with the year of observation 2013-2015 so that the overall sample amounted to 69. Types of data used in this study is quantitative data. The data source of this research is secondary data, in the form of financial statements Analysis of data using multiple linear regression. The results showed: partially profitability, profit growth, business effectiveness and investment opportunity set have a significant effect on dividend policy. Meanwhile, managerial ownership has no significant effect on dividend policy, simultaneously shows that profitability, managerial ownership, profit growth, business effectiveness and investment opportunity set have a significant effect on dividend policy.Keywords : profitability, managerial ownership, corporate growth, business effectiveness, and Investment Opportunity Set, Dividend Policy